Majorana bound states in hybrid quantum dot-topological superconducting nanowires: detection and applications - Ricco, Luciano Henrique Siliano (2020)
In the last years, the seeking for Majorana quasiparticles has been one of the hottest topics in condensed matter physics, owing to its potential application for achieving fault-tolerant quantum computing pro- cesses. Such exotic quasiparticles emerge as bound states at the ends of one-dimensional (1D) spinless p-wave superconductors within topologically protected phases. An indicative of this so-called Majorana bound states (MBSs) in these 1D systems is given by the emergence of a robust zero-bias conductance peak (ZBCP) in tunneling spectroscopy measurements. However, other physical phenomena can give rise to such a peak, as Kondo effect, disorder and Andreev bound states (ABSs), for instance. Concerning this later, such states can stick at zero energy even when parameters as magnetic field or chemical potential are changed, thus perfectly mimicking the MBSs hallmark. Hence, distinguishing between trivial ABSs and topologically protected MBSs is one of the current key issues in the filed of Majorana detection. Aiming to enlarge the discussion concerning the MBS-ABS distinction, in this thesis we study the electronic transport features of a hybrid device composed by a quantum dot coupled to a topological superconducting nanowire hosting MBSs at the ends, wherein the so-called degree of Majorana nonlocality is taken into account. In this scenario [Phys. Rev. B 98, 075142 (2018)], we analyze the role of the Fano interference phenomenon in the well-known Majorana oscillations, showing that both shape and amplitude of such oscillatory patterns depend on the bias voltage, degree of MBSs nonlocality, and Fano parameter of the system. We also demonstrate that the spin-resolved density of states of the dot responsible for the zero-bias conductance peak strongly depends on the separation between the MBSs and their relative couplings with the dot [Phys. Rev. B 99, 155159 (2019)], suggesting that spin-resolved spectroscopy can be used as a tool for discriminating between ABSs and MBSs. It is worth noticing that in both works we recover experimental profiles, at least qualitatively. Moreover, along the current thesis we propose a quantum bit storing/reading mechanism [Phys. Rev. B 93, 165116 (2016)] and a thermoelectrical hybrid device [Sci. Reports, 8, 2790 (2018)], both based on MBSs properties.